IMPLEMENTASI PEMBERIAN TEKNIK BATUK EFEKTIF PADA KLIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) UNTUK MENGELUARKAN SPUTUM - Nurzanah, Eka; Saragih, Julwansyah (Jurnal Keperawatan Karya Bhakti, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a lung disorder that occurs over a long period of time / chronically characterized by obstruction of airflow in the respiratory tract. One of the nursing problems that arise in COPD cases is ineffective airway clearance. Efforts made to overcome airway clearance include providing effective cough techniques. Objectives: being able to perform and apply nursing care to patients with Chronic Obstructive Pulmonary Disease (COPD) with the implementation of effective coughing techniques to remove sputum at Vita Insani Hospital Pematangsiantar. Methods: This research design is quantitative-descriptive using a case study approach. The research sample consisted of 2 respondents, namely patients with chronic obstructive pulmonary disease (COPD). The sampling used in this study was purposive sampling. Data collection was carried out using observation techniques, interviews, physical examinations, supporting examinations, documentation conducted on April 24, 2024-26 April 2024 at Vita Insani Hospital Pematangsiantar. Results: the results of this case study indicate that after implementation by providing an effective cough for 3 days the results obtained that both clients experienced a decrease in respiratory frequency and sputum could be removed, vesicular breath sounds, regular breathing rhythms and sonorous lung percussion in both clients